Wandel in der Geldpolitik und Ausweitung der europäischen Schuldenkrise - Rohde, Armin (Estonian Discussions on Economic Policy, 2013)
In the present paper fundamental changes in monetary policy strategy, especially in leading industrialized countries, from concentrating on development of the quantity of money to focusing strictly on developments of interest rates and interest rate levels is analysed in the case of the European Central Bank. The goal of research is to show that this change in monetary policy is one important reason for expansions of the European debt crisis since 2010. Within this new monetary policy regime, interest rate levels on the one hand and the transmission of interest rate policy measures to the interest rates of the other financial markets on the other hand, have become a very important role in central banking policies of today. For example to guarantee a sure and strict transmission of interest rate policy measures, which have its starting point on the short-term money market, and which should radiate to long-term interest rates on the capital market the ECB, if necessary, uses outright monetary transactions in secondary markets for sovereign bonds in the euro area. The main reason for acting in that manner is to avoid rising of long-term interest rates and to guarantee low levels of interest rate in the sovereign bonds markets. It is argued in the present paper that in focusing to guarantee low interest rate levels especially to overcome economic crisis you can find one important reason for expansions of the European debt crisis. This is so, because in view of current European economic policy rising interest rates in the European bonds markets above a level of 6 or 7 percent have become an unmistakeable proof of a severe debt problem.